2018
DOI: 10.1177/000313481808400745
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Trauma Center Volume on Observed/Expected Mortality: Does Size Matter?

Abstract: Relationship between trauma center patient volume (TCV) and mortality remains inconclusive. Our aim was to determine the relationship between TCVs and observed/expected (O/E) all-cause mortality. This is the first study to evaluate the relationship between trauma center (TC) volumes and O/E all-cause mortality with no exclusion. Review of prospectively collected data from 94 TCs using the National Sample Program from the National Trauma Data Bank 2013. TCs were stratified into five groups based on TCV: <701… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Studies suggest that higher patient volumes are associated with better outcomes because of center-level expertise. 5,[30][31][32] Adding trauma centers in areas without access may improve access to trauma care; conversely, adding trauma centers in areas without access issues may lead to dilution of expertise and lower patient volumes for those centers. 33,34 In Ohio, a statewide analysis demonstrated that a greater number of level I centers in a county or region was associated with slightly higher mortality compared with counties and regions with only one level I center.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that higher patient volumes are associated with better outcomes because of center-level expertise. 5,[30][31][32] Adding trauma centers in areas without access may improve access to trauma care; conversely, adding trauma centers in areas without access issues may lead to dilution of expertise and lower patient volumes for those centers. 33,34 In Ohio, a statewide analysis demonstrated that a greater number of level I centers in a county or region was associated with slightly higher mortality compared with counties and regions with only one level I center.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, high TCV centers admit greater than 1200 patients annually, whereas low TCV centers admit less. [11] This higher volume could result in higher complication rates and cause the higher mortality rates. For instance, Tepas et al [12] evaluated the relationship between case volume and outcome as measured by mortality, and found a trend of increasing mortality with increasing volume, despite a consistent proportion of severe injury.…”
Section: Discussionmentioning
confidence: 99%
“…Both ACS and State Level 1 and 2 TCs had on average volumes above 1200 admissions per year, which is well above the 650-admission threshold determined by Nathens et al [11] for significantly improved outcomes. A similar study by Elkbuli et al [9] investigated the relationship between TCVs and observed/expected (O/E) all-cause mortality and found that higher TC volumes are correlated with higher injury severity and lower O/E mortality. This may indicate that TCV above a certain threshold is beneficial to patient outcomes and that the “threshold” effect is confirmed.…”
Section: Discussionmentioning
confidence: 96%
“…Generally, high TCV centers admit greater than 1200 patients annually while low TCV centers admit less. [9] A Shapiro-Wilk test was used to test for normality/skewness in TCV and injury distribution among ACS and State Level 1 and 2 TCs. To adjust for skewness in ISS data distribution among ACS and State Level 1 and 2 TCs, we used adjusted all-cause mortality (O/E mortality) as our primary outcome.…”
Section: Introductionmentioning
confidence: 99%